SEISMIC RISK ASSESSMENT FOR LARGE ROMANIAN DAMS ON BISTRITA AND SIRET RIVERS AND THEIR TRIBUTARIES - MOLDOVAN, Iren-Adelina; TOMA-DĂNILĂ, Dragoş; CONSTANTIN, Angela Petruţa; PLĂCINTĂ, Anica Otilia; POPESCU, Emilia; GHIŢĂ, Cristian; DIACONESCU, Mihail; MOLDOVEANU, Traian; PAERELE, Cosmin Marian (Studia Universitatis Babeș-Bolyai Ambientum, 2016)
The most important specific requirements towards dams’ safety is the seismic risk assessment. This objective will be accomplished by rating the dams into seismic risk classes using the theory of Bureau and Ballentine, 2002, and Bureau (2003), taking into account the maximum expected peak ground motions at dams’ site, the structures vulnerability and the downstream risk characteristics. The maximum expected values for ground motions at dams’ site have been obtained using probabilistic seismic hazard assessment approaches (PSHA) for dams situated on Bistrita and Siret Rivers and their tributaries. The structural vulnerability was obtained from dams’ characteristics (age, high, water volume) and the downstream risk was assessed taking into account human, economical, touristic, historic and cultural heritage from the areas that might be flooded in the case of a dam failure. The results of the work consist of local and regional seismic information, specific characteristics and locations of dams, seismic hazard values and risk classes, for all sites. The studies undertaken in this paper have as final goal to provide the local emergency services with warnings of a potential dam failure and ensuing flood, for the near future, as a result of a large earthquake occurrence, allowing further public training for evacuation.